Enzymatic Biodegradation of Polyethylene Terephthalate (PET) by Crude Lipase from Geotrichum candidum - Nurul Haviza; Armaini; Syafrizayanti Syafrizayanti (Indonesian Scholar Society, 2025)
The issue of plastic waste, particularly polyethylene terephthalate (PET), has become a major global environmental concern due to its resistance to natural degradation. One promising approach to addressing PET waste is the use of lipase enzymes produced by microorganisms. This study aims to explore the potential of the fungus Geotrichum candidum J1 to produce crude lipase enzymes capable of degrading PET plastic. The research involved stages including isolation and rejuvenation of the fungus, enzyme production through solid-state fermentation, and lipase activity assay using the cup-plate method. Subsequently, PET degradation testing was carried out using the crude enzyme extract under controlled conditions for 30 days. The results indicated that the crude lipase from G. candidum J1 exhibited lipolytic activity, as evidenced by clear zones formed on selective media. The average total protein yield reached 2.992 ± 0.05 mg/mL, indicating stable fermentation. Degradation tests showed a weight loss of PET between 5.9% and 6.4%. Characterization by Fourier Transform Infra Red (FTIR) confirmed the cleavage of ester bonds in PET structure, evidenced by spectral changes in carbonyl groups. Observations using a Scanning Electron Microscope (SEM) revealed morphological changes, including cracks and pores, on the PET surface post-treatment. In conclusion, the crude lipase from G. candidum J1 demonstrates significant potential as a biodegradation agent for reducing PET plastic pollution in an environmentally friendly manner.